1988
DOI: 10.1139/x88-110
|View full text |Cite
|
Sign up to set email alerts
|

The adjustment of growth, sapwood area, heartwood area, and sapwood saturated permeability of balsam fir after different intensities of pruning

Abstract: Balsam fir trees established from advanced regeneration following a clear-cut in 1970 were pruned in June 1985 to live crown ratios of 0.6, 0.4, and 0.2 compared with control trees, which had live crown ratios of 0.8. After two growing seasons, we investigated the homeostatic adjustment of these trees to the loss of their foliage. The height growth, basal area growth, sapwood cross-sectional area, heartwood area, and sapwood saturated permeability of the trees that were pruned to a 0.6 live crown ratio were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…Ericsson (1966) reported lower heartwood content in thinned stands (33%) than in unthinned stands (40%) in a survey study on Pinus sylvestris stands. Margolis et al (1988) reported an increased heartwood area in heavily pruned Abies balsamea trees. In a study on the effects of pruning regimes in 25-year-old Pinus sylvestris by Långström and Hellqvist (1991), pruning reduced growth and increased heartwood area.…”
Section: Tectona Grandis Plantations In Costa Ricamentioning
confidence: 98%
“…Ericsson (1966) reported lower heartwood content in thinned stands (33%) than in unthinned stands (40%) in a survey study on Pinus sylvestris stands. Margolis et al (1988) reported an increased heartwood area in heavily pruned Abies balsamea trees. In a study on the effects of pruning regimes in 25-year-old Pinus sylvestris by Långström and Hellqvist (1991), pruning reduced growth and increased heartwood area.…”
Section: Tectona Grandis Plantations In Costa Ricamentioning
confidence: 98%
“…For species other than teak, Margolis et al (1988) consider that the unstained center of the stem, which can be interpreted as heartwood, may be temporarily immobilized sapwood rather than true heartwood; this explains the difficulty to establish the boundary between heartwood and sapwood, and could be used eventually as an indicator of stress. These authors report an increment in heartwood area in heavily pruned Abies balsamea (L.) Mill.…”
Section: Wood Qualitymentioning
confidence: 99%
“…The area of sapwood ring is frequently calculated by researchers as a value used to describe conducting area and relate it to biometric traits of tree crowns (Ganskopp, Miller 1986;Dean et al 1988;Margolis et al 1988;Mörling, Valinger 1999;McDowell et al 2002;Medhurst, Beadle 2002;Sellin, Kupper 2003;Stancioiu, O'Hara 2005;Longuetaud et al 2006). However, the areas of late wood ring contained within sapwood, neither participating nor involved in water conduction to a limited extent, result in a situation when the sapwood area reduced by the area of late wood, i.e.…”
Section: Discussionmentioning
confidence: 99%